Minimising Vegetable Production Constraints in Hills: Boon to Attain Sustainable Vegetable Farming System - Singh, Surinder; Hansra, B.S. (Indian Journal of Extension Education, 2021)
In Himachal Pradesh Vegetable cultivation is done on steep hilly farms and has some inherent constraints which differentiate hill farming to that of plains. Present study was conducted in hilly state Himachal Pradesh to compare vegetable production constraints as perceived by self help group member and non-member farmers in case of SHG members, constraint of high cost of inputs, monkey menaces & stray animals and more distance from market, lack of irrigation sources, whereas, poor knowledge about enterprise, lack of entrepreneurship development oriented training and more distance from market were major constraints for non-members. Non members farmers perceived significantly higher constraints than SHG member farmers. Cognitive and extension activities constraints were well addressed by SHG approach and there is need to bring maximum vegetable growers under the preamble of SHG to achieve sustainability. Also sufficient village road connectivity, modern storage facilities, community irrigation facilities, quality input sale centres, protection from wild animals and mechanization of small farms required to be done in vegetable growing areas to make vegetable farming sustainable.
Keywords: Constraints; Farming; Minimising; Production; Sustainable; Vegetable